The Prevalence of Fear of Childbirth and Its Association With Intolerance of Uncertainty and Coping Styles Among Pregnant Chinese Women During the COVID-19 Pandemic - Han, Lingli; Bai, Hua; Lun, Bing; Li, Yanxia; Wang, Yingfan; Ni, Qingnan (Frontiers in Psychiatry, 2022)
Background: Fear of childbirth (FOC) is one of the most common psychological symptoms among pregnant women and significantly relates to cesarean section, anxiety, and depression. However, it is not clear the prevalence and risk factors of FOC among Chinese pregnant women since the outbreak of the COVID-19 pandemic. Aims: The objective of this study was to examine the associations between coping styles, intolerance of uncertainty, and FOC. Method: From December 2021 to April 2022, a cross-sectional survey was conducted in two hospitals in China through convenient sampling. The cross-sectional survey was conducted among 969 pregnant women, which included the Childbirth Attitude Questionnaire (CAQ), Intolerance of Uncertainty Scale-12 (IUS-12), and Simplified Coping Style Questionnaire (SCSQ). Results: The total prevalence of FOC was 67.8%. The percentages of women with mild (score of 28–39), moderate (40–51), and severe FOC (52–64) were 43.6, 20.2, and 4.0%, respectively. The regression results indicated that primiparas, unplanned pregnancy, few spousal support, intolerance of uncertainty, and negative coping styles were significant risk factors for FOC. Women who adopt positive coping strategies experience a lower level of childbirth fear. Conclusion: These findings suggest that cultivating positive coping styles and obtaining sufficient childbirth information may be helpful for mothers’ mental health. Regular screening assessment of perinatal psychological symptoms, such as the high level of intolerance of uncertainty and negative coping styles, should be adopted to reduce the risk of fear of childbirth.